Mat-forming lichens affect microclimate and litter decomposition by different mechanisms. (April 2020) - van Zuijlen, Kristel; Roos, Ruben E.; Klanderud, Kari; Lang, Simone I.; Asplund, Johan
Abstract: We studied the effects of different mat-forming lichens on microclimate and litter decomposition in an alpine ecosystem where lichens constitute a major part of the vegetation. We used four lichens with contrasting colour and water-holding capacity. We recorded soil temperature and moisture, and decomposition rate of plant litter under the different lichen mats and in bare soil. While soil temperature and freeze-thaw cycles were reduced under all lichen mats compared to bare soil, Cladonia rangiferina/ Cladonia stygia insulated stronger than other lichens. Litter decomposition was faster under Flavocetraria nivalis than under Alectoria ochroleuca, but this was not related to lichen traits or microclimate. We conclude that insulation by lichen mats is stronger with higher water-holding capacity, and we suggest that microbial communities associated with different lichens have a larger effect on litter decomposition than soil conditions. Our findings highlight the importance of mat-forming lichens on microclimate and ecosystem processes in alpine environments.